State-of-the-Art Materials Science in Belgium 2017 - Dirk Poelman (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
ca. 200 words; this text will present the book in all promotional forms (e.g. flyers). Please describe the book in straightforward and consumer-friendly terms. Belgium is a small country. The days of mining minerals and ores from the former colony, Congo, have long passed by and the last coal mine was closed 25 years ago. Now, there are hardly any physical resources in Belgium which can be exploited in materials research and development or industry. Materials research in Belgium bypasses this drawback by focussing on highly technological research fields, not requiring vast amounts of raw material. This approach includes the development of new analytical methods for the characterization of materials, research into new advanced functional materials as well as defining new industrial processes utilizing existing materials. This book compiles recent review and research papers from Belgian universities, covering a wide range of research disciplines in materials science. It thus presents a contemporary view on materials research activities in Belgium.